Drugs, Crime and Social Exclusion. Social Context and Social Theory in British Drugs-Crime Research - Seddon, Toby (The British journal of criminology, 2006)
The association between drugs and crime is one of the central concerns of contemporary British drugs research and policy. Another major concern in recent years has been the clustering together of the most serious problems of drugs and crime in neighbourhoods already experiencing multiple social and economic difficulties. This paper seeks, first of all, to re-situate the drug-crime nexus in its full social context in order to provide a new perspective on these two key aspects of the British drug problem today. In doing so, the analysis raises in applied form some important issues in criminological theory and the paper attempts, secondly, to make a contribution to these theoretical debates